2020
DOI: 10.1136/archdischild-2019-318346
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation alongside the Speed of Increasing milk Feeds Trial (SIFT)

Abstract: ObjectiveTo evaluate the cost-effectiveness of two rates of enteral feed advancement (18 vs 30 mL/kg/day) in very preterm and very low birth weight infants.DesignWithin-trial economic evaluation alongside a multicentre, two-arm parallel group, randomised controlled trial (Speed of Increasing milk Feeds Trial).Setting55 UK neonatal units from May 2013 to June 2015.PatientsInfants born <32 weeks’ gestation or <1500 g, receiving less than 30 mL/kg/day of milk at trial enrolment. Infants with a known severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, faster feeding was associated with an increased risk of moderate or severe motor impairment (adjusted effect 1.48, CI 1.02 to 2.14). An associated cost analysis identified that this excess of motor impairment meant that faster feeds are both clinically and economically undesirable 32…”
Section: Barriers To Achieving Nutritional Targetsmentioning
confidence: 99%
“…However, faster feeding was associated with an increased risk of moderate or severe motor impairment (adjusted effect 1.48, CI 1.02 to 2.14). An associated cost analysis identified that this excess of motor impairment meant that faster feeds are both clinically and economically undesirable 32…”
Section: Barriers To Achieving Nutritional Targetsmentioning
confidence: 99%